Telephone versus self administration of outcome measures in low back pain patients - KARADAĞ SAYGI, NAİME EVRİM; ŞENCAN, SAVAŞ (KARE PUBL, 2018)
Objectives: Comparison of self-rating method and telephone interview method on outcome measures' results. Methods: This cross-sectional study included 100 patients aged 18-40 years who applied to Physical Medicine and Rehabilitation outpatient clinics with mechanical low back pain. Outcome measures [Oswestry Disability Index (ODI), Roland Morris Disability Questionnaire (RMDI), Numeric Pain Rating Scale (NPRS), Istanbul Low Back Pain Disability Index (ILBPD] were administered, and the duration of administration was recorded by two different methods. The self-assessment method and scales were administered by patients in the outpatient clinic and the telephone interview method; scales were administered by the researcher via telephone-calls 24 hours after the out-patient visit. Results: There were no significant differences observed in the results of outcome measures by the method of administration except the Istanbul Low-Back-Pain Disability Index (p=0.030). Outcome measures' results were highly correlated with one another when administered by different methods and orders of administration. Duration of administration was significantly shorter when outcome measures were administered by telephone interview (p<0.001). Conclusion: Different methods of administration usually do not have an impact on outcome measure results. However, in some scales like ILBPDI, it may emerge as a factor affecting outcome measures' results. Therefore, adherence to an initially preferred administration method throughout the follow-up period is important regarding the reliability of the results.
Keywords: Low back pain; scale administration methods; telephone versus self administration; QUALITY-OF-LIFE; FUNCTIONAL DISABILITY; TURKISH VERSION; VALIDATION; COST; ILLNESS; INDEX